Strengthening Infection Control through Interdepartmental Cooperation: A Review of Collaboration between Medical Departments and Infection Prevention Units - Alaallah, Asrar Esmaail; Alyami, Nasser Ali Duhyman; Al-Rubaie, Hadi Abdullah Ali; Hattan, Thekra Mudhhi; al Mohammed , Hadi Mohammed; Alyami, Saad Saud; Makeen, Nawal Ahmed; Masmali, Amani Musleh Ali; Al Saleh, Saleh Eidhah Ahmed; Alhaddad, Mohammed Ahmad Mohammed (Journal of Posthumanism, 2024)
Infection prevention and control (IPC) remains a cornerstone of patient safety and quality healthcare delivery. The effective reduction of healthcare-associated infections (HAIs) requires not only robust infection control protocols but also sustained interdepartmental cooperation, particularly between medical departments and infection prevention units. This review explores the nature and impact of collaborative efforts aimed at strengthening infection control practices in healthcare institutions. Through an analysis of recent literature and institutional experiences, the article identifies key factors that enable successful cooperation, such as leadership support, joint training, communication mechanisms, and shared accountability. It also addresses the organizational and cultural barriers that hinder collaboration, including departmental silos and limited physician engagement in IPC activities. The review concludes by offering strategic recommendations for fostering stronger integration between medical teams and infection control units to enhance compliance, reduce infection rates, and improve overall healthcare outcomes.